Herbicide selection for weed control and effect on rubber seedlings - Lima, Adelise de Almeida (Pesquisa Agropecuaria Brasileira, 2014)
The effect of eight herbicides applied on four weeds, directly into the soil and on 30cm height rubber seedlings (Hevea spp.), was studied under green-house conditions. The weeds Digitaria insularis, Paspalum conjugatum, Synedrella nodiflora, and Bidens pilosa. The herbicides used were glifosate at 1.5 kg a.i./ha, amonio-glutosinate at 1.0 kg a.i./ha, asulam-diuron at 5.0 kg a.i./ha, glifosate + frigate at 1.2 + 1.3 kg a.i./ha, 2,4-D-glifosate at 2.0 kg a.i./ha, MSMA + diuron at 2.5 + 2.0 kg a.i./ha and simazine-paraquat at 4 kg a.i./ha. The results, evaluated through visual evaluation, and root, top and total dry weight of rubber seedlings showed that 2,4-D-glifosate, glifosate, MSMA + diuron and glifosate + trigate efficiently controlled the weeds without causing toxicity to the rubber seedlings. These products could be used on field were those weeds predominate